2020
DOI: 10.5306/wjco.v11.i6.320
|View full text |Cite
|
Sign up to set email alerts
|

Active surveillance in low risk papillary thyroid carcinoma

Abstract: In recent decades, while the incidence of thyroid cancer has increased exponentially around the world, mortality has remained stable. The vast majority of this increase is attributable to the identification of intrathyroidal papillary microcarcinomas, which exhibit slow growth rates with indolent courses. A diagnosis of thyroid cancer based upon the presence of these small tumors could be considered as an overdiagnosis, as the majority of these tumors would not likely result in death if left untreated. Althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 75 publications
(216 reference statements)
0
12
0
Order By: Relevance
“…The incidence of thyroid cancer has been increasing rapidly in recent years, and the largest increase in incidence of all cancers was seen for thyroid cancer in China [2] . The reason might due to the rapid development of imaging detection technologies and increasing awareness of people's health [3] , especially considering that thyroid cancer mortality remained stable at a rate of approximately 0.5 cases per 100000 persons [4] . Thyroid cancers are divided into four main sub-types(papillary, follicular, medullary, and undifferentiated cancers) [5] .To date, the mechanism of thyroid carcinogenesis remains incompletely understood, and the only well-established risk factor for thyroid cancer might be exposure to ionizing radiation [6] .…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of thyroid cancer has been increasing rapidly in recent years, and the largest increase in incidence of all cancers was seen for thyroid cancer in China [2] . The reason might due to the rapid development of imaging detection technologies and increasing awareness of people's health [3] , especially considering that thyroid cancer mortality remained stable at a rate of approximately 0.5 cases per 100000 persons [4] . Thyroid cancers are divided into four main sub-types(papillary, follicular, medullary, and undifferentiated cancers) [5] .To date, the mechanism of thyroid carcinogenesis remains incompletely understood, and the only well-established risk factor for thyroid cancer might be exposure to ionizing radiation [6] .…”
Section: Introductionmentioning
confidence: 99%
“…In another study of nonoperative management of elderly PTMC patients aged >65 years, the overall 5-year survival rate was lower, 23% [42]. In addition, in a recent study, Pitoia et al [8] summarized the clinical outcomes of active surveillance around the world, and the rate of tumor growth larger than 3 mm and lymph node metastasis could reach 22% and 3.8%, respectively. All these results suggested that even small-sized PTC tumors might require active therapeutic intervention, in particular for aged patients.…”
Section: Discussionmentioning
confidence: 99%
“…Papillary thyroid carcinoma (PTC) is a well-differentiated malignant thyroid tumor. PTC accounts for the majority of thyroid cancers, but it is an indolent tumor [4,5] with a good prognosis [6][7][8]. More than 50% of PTCs are less than 1 cm in size and are referred to as papillary thyroid microcarcinoma (PTMC) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Presently, overdiagnosis and overtreatment of PTC is one of the most controversial issues in the management of thyroid carcinoma (11,12). Long-term active surveillance (AS) of patients with T1aN0M0 PTC performed in several institutions has revealed that the follow-up approach may constitute an appropriate, conservative management strategy (13)(14)(15). The 2015 ATA Management Guidelines for Adult Patients with Thyroid Nodules and Differentiated Thyroid Cancer also mentioned that AS may be employed as an alternative strategy in selected PTC patients (4).…”
Section: Introductionmentioning
confidence: 99%